Pengaruh Puasa Secara Periodik Terhadap Kinerja Pertumbuhan Ikan Nila Salin Oreochromis niloticus - Awan Sustiawan; Asni Anwar; Akmaluddin Akmaluddin; Burhanuddin Burhanuddin; Harnita Agusanty; Murni Murni; Muhammad Syaiful Saleh; Ratna Ratna (Jurnal Perikanan Unram, 2024)
Saline tilapia (Oreochromis niloticus) is Indonesia's leading cultivation commodity and has important economic value. The general problem in increasing O. niloticus production is the high cost of feed. Feed starvation is an alternative to increase feed utilization efficiency and growth performance. The aim of this research was to determine the effect of periodic feed starvation on the growth of saline tilapia. The research was designed in a completely randomized design, four treatments with three replications with different levels of food fasting, namely treatment A: Daily feeding without periodic fasting, Treatment B: 1 day fasting, 3 days fasting periodically, treatment C: 1 day fasting. 5 days fed periodically, treatment D: 1 day fasted 7 days fed periodically. A total of 120 saline tilapia fry were reared for 35 days, given a feed dose of 3% of body weight. The results of the research showed that saline tilapia seeds treated with 1 day fasting for 7 days and fed periodically produced the highest feed efficiency (0.58%), feed conversion ratio (2) and daily growth rate (0.14%) compared to other treatments.